Biology of M argarodes vredendalensis De Klerk (Coccoidea: Margarodiae) in South Africa - De Klerk, C. A (South African Journal of Enology and Viticulture, 2017)
Various aspects of the biology of Margarodes vredendalensis De Klerk, a vine infesting species, were studied. Under laboratory conditions adult females emerged during January and February, and only 10-16% of the cysts developed into females annually. Although cysts were detached from their host plant, females emerged during four successive years from the same population. Adult females did not migrate to the soil surface for mating, and reproduced parthenogenetically. The average oviposition period of females was 18 days, and their average lifespan 40 days. An average of 507 eggs per female were oviposited, the highest number being produced during the first 9 days. The effects of temperature, relative humidity and soil moisture on oviposition, as well as on incubation of the eggs, are reported on. Cysts in the field were found to a depth of 1,2 m in the soil, the highest number occurring at a depth of 46-60 cm. The vertical distribution of cysts was directly related to the vertical distribution of roots. Significant negative correlations were also found between the vertical distribution of cysts and soil moisture, as well as the percentage clay of the soil.